Metal‐Free Dual Modal Contrast Agents Based on Fluorographene Quantum Dots. (21st October 2016) - Radhakrishnan, Sruthi; Samanta, Atanu; Sudeep, Parambath M.; Maldonado, Kiersten L.; Mani, Sendurai A.; Acharya, Ghanashyam; Tiwary, Chandra Sekhar; Singh, Abhishek K.; Ajayan, Pulickel M.
Abstract : Nonfunctionalized and functionalized fluorographene systems are studied of which acid functionalized system shows greater magnetic moment. This is experimentally verified and the hysteresis and low temperature studies reveal paramagnetic behaviour. The inherent paramagnetism along with the fluorine content is utilized in its development as a dual modal agent for proton and 19 F MRI.